Level Up With Problem-Based Learning Students’ Perception Of Its Impact On Learning In Efl Context - Khoiriyah, Nisa; Perdana , Purnama Rika; Fitriani, Dini (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to investigate the impact of Problem-Based Learning (PBL) on the outcomes of the 9th-grade students in an English language learning context. Drawing on theories of PBL and previous research, the study employs a surveying approach to explore students' perceptions and performance following PBL implementation. The findings reveal a positive result of PBL from students’ perception, demonstrating improvements in understanding course materials, critical thinking, problem-solving skills, self-directed learning, confidence in knowledge application, and finally their scores. Additionally, students show increased engagement and motivation in PBL activities, attributing it to the relevance and appeal of presented problems. These results emphasize the efficacy of PBL in enhancing students’ experiences and preparing them for real-world challenges.